Evolution of continental temperature seasonality from the Eocene greenhouse to the Oligocene icehouse –a model–data comparison - A. Toumoulin; D. Tardif; Y. Donnadieu; A. Licht; J.-B. Ladant; L. Kunzmann; G. Dupont-Nivet (Climate of the Past, 2022)
At the junction of greenhouse and icehouse climate states, the Eocene–Oligocene Transition (EOT) is a key moment in Cenozoic climate history. While it is associated with severe extinctions and biodiversity turnovers on land, the role of terrestrial climate evolution remains poorly resolved, especially the associated changes in seasonality. Some paleobotanical and geochemical continental records in parts of the Northern Hemisphere suggest the EOT is associated with a marked cooling in winter, leading to the development of more pronounced seasons (i.e., an increase in the mean annual range of temperature, MATR). However, the MATR increase has been barely studied by climate models and large uncertainties remain on its origin, geographical extent and impact. In order to better understand and describe temperature seasonality changes between the middle Eocene and the early Oligocene, we use the Earth system model IPSL-CM5A2 and a set of simulations reconstructing the EOT through three major climate forcings: p CO 2 decrease (1120, 840 and 560 ppm), the Antarctic ice-sheet (AIS) formation and the associated sea-level decrease. Our simulations suggest that p CO 2 lowering alone is not sufficient to explain the seasonality evolution described by the data through the EOT but rather that the combined effects of p CO 2 , AIS formation and increased continentality provide the best data–model agreement. p CO 2 decrease induces a zonal pattern with alternating increasing and decreasing seasonality bands particularly strong in the northern high latitudes (up to 8 ∘ C MATR increase) due to sea-ice and surface albedo feedback. Conversely, the onset of the AIS is responsible for a more constant surface albedo yearly, which leads to a strong decrease in seasonality in the southern midlatitudes to high latitudes ( ><mn ...